ChemInform Abstract: Benzimidazolin‐2‐ylidene N‐Heterocyclic Carbene Complexes of Ruthenium as a Simple Catalyst for the N‐Alkylation of Amines Using Alcohols and Diols. Issue 24 (June 2015) - Shan, Siah Pei; Xiaoke, Xie; Gnanaprakasam, Boopathy; Dang, Tuan Thanh; Ramalingam, Balamurugan; Huynh, Han Vinh; Seayad, Abdul Majeed
Abstract: Simple air and moisture stable ruthenium complexes are synthesized from readily available benzannulated N‐heterocyclic carbene ligands and applied as catalysts for the alkylation of various amines using alcohols under solvent‐free conditions.